Today as a Transinformativity - Augistinaitis, Arūnas (Sociologija. Mintis ir veiksmas, 1999)
The article aims to discuss the postmodern knowledge and to understand the dynamic nature of the discursive formation. The author argues that the postmodern knowledge is connected with the theory of information, in which the difference between epistemological and philosophical discourses diminishes. The author suggests that the theory of information itself justifies the informational postmodern knowledge and defines the object of both theoretical and philosophical analysis.